The Influence Of Work Motivation And Competency On Work Discipline Of Employee at The Ministry of Cooperation, PERINDAG, Tasikmalaya City - Moch Tomi Gunawan; Barin Barlian; Arga Sutrisna (Penerbit Jurnal Indonesia, 2023)
This study aims to determine and analyze the influence of work motivation and competence on work discipline of employees at the Cooperative Service Office of UMKM Perindag Kota Tasikmalaya. The method used in this research is descriptive analysis research method with a quantitative approach. With a research sample of 67 (sixty seven) employees of the Tasikmalaya City Cooperative, UMKM, Perindag Office. The data used in this study are secondary data and primary data. The analytical tool used in this study is multiple linear regression using SPSS 25. The results show that work motivation, competence and work discipline have a very good classification for employees of the UMKM Cooperative Office of Industry and Trade. Tasikmalaya City. Based on the results of the research that Work Motivation and Competence simultaneously have a significant effect on the Work Discipline of the employees of the UMKM Cooperative Office of Industry and Trade Tasikmalaya City. Work Motivation Partially has a significant effect on the Work Discipline of the employees of the Cooperative Office of UMKM Industry and Trade Tasikmalaya City. Competence Partially has a significant effect on the Work Discipline of the employees of the Cooperative, UMKM, Industry and Trade Office, Tasikmalaya City.